Effect of Cannabinoid Receptor Agonists on Isolated Rat Atria. Issue 4 (October 2018) - Maggo, Simran; Ashton, John C.
Abstract : Abstract: Cannabinoid CB2 receptor agonists are under investigation for clinical use. At the same time, synthetic cannabinoids have been implicated in a number of deaths. One cause of death is thought to be cardiac arrest subsequent to extreme tachycardia. Central mechanisms are thought to play a role in this, with CB1 but not CB2 receptors thought to mediate central effects. However, the direct effects of cannabinoids on the heart are less well understood. We therefore tested the effects of cannabinoids on isolated rat atria to test whether activation of myocardial CB1 and CB2 receptors could contribute to tachycardia. Although we found a moderate effect that can be attributed to CB1 receptors, we did not find any evidence for chronotropic effects by a CB2 receptor activation. Our results indicate that cannabinoid cardiotoxicity may partially involve CB1 receptors in the myocardium, and that CB2 receptor agonists are unlikely to have significant effects on the heart.